Optimization of the placement and capacity of small-scale generation sources in distribution power networks - Abdurakhim D. Taslimov; A'zam I. Turaev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: At present, the integration of low-power generation sources into electrical power systems is one of the most relevant research areas worldwide. The use of such sources enhances the reliability of power supply, reduces the load on centralized grids, and decreases energy losses. Furthermore, the application of renewable and environmentally friendly energy sources is a priority direction of the national energy policy, playing a crucial role in ensuring the stability and efficiency of power systems. Aim: The main objective of the research is to minimize electrical energy losses by determining the optimal placement points and power capacities of low-power generation sources in distribution networks. Achieving this goal allows for stabilizing the operation mode of distribution systems, normalizing voltage levels, and improving the overall energy efficiency of the grid. Methods: The study employs a mixed nonlinear integer programming model. To obtain the optimal solution, a modified Kelley cutting-plane method and genetic algorithms were applied. Computational modeling was carried out using the GAMS (General Algebraic Modeling System) and RASTR software environments. An experimental model based on a 30-node radial distribution network was developed to analyze voltage parameters and power losses. Results: Modeling results indicate that installing a 2.055 MW distributed generation source at node No. 7 reduces active power losses from 218 kW to 113.7 kW. This confirms the efficiency of the proposed optimization approach and its practical significance for improving the operating conditions of electrical distribution networks. The obtained results show good agreement with full-variant calculations, which validates the reliability of the proposed methodology.